Unveiling the fungal frontier: Exploring pediatric surgical cases with bowel mucormycosis through a retrospective lens - Parveen Kumar; Vivek Manchanda; Chhabi Ranu Gupta; Arti Khatri (EL-Med-Pub, 2024)
Background: Bowel mucormycosis is common among high-risk surgical neonates and has high fatality. This study was done to study the clinical profile and outcome of pediatric surgical patients operated at our center who had bowel mucormycosis on histology. Methods: It was a retrospective observational study. The data was collected from the medical records department. The files of surgical patients with tissue diagnosis of bowel mucormycosis operated at Chacha Nehru Bal Chikitsalaya from June 2018 to May 2021 were retrieved. The data was tabulated on Microsoft Excel sheet®. Results: A total of 11 surgical patients with bowel mucormycosis on histology were traced. The study had male preponderance. The majority were neonates and had low platelet counts with raised CRP levels. All but one expired, with severe sepsis and septic shock as major causes of death. Conclusion: The invasive mucormycosis is more common among neonates (but older children are not immune) with male preponderance. It may affect any part of GIT and the counts and sepsis screen may be normal. It has a high fatality rate.